Effects of Arm-Crank Exercise on Fitness and Health in Adults With Chronic Spinal Cord Injury: A Systematic Review - Chiou, Shin Yi; Clarke, Emma; Lam, Chi; Harvey, Tom; Nightingale, Tom E. (Frontiers in Physiology, 2022)
Individuals with spinal cord injury (SCI) may benefit less from exercise training due to consequences of their injury, leading to lower cardiorespiratory fitness and higher risks of developing cardiovascular diseases. Arm-crank exercise (ACE) is the most common form of volitional aerobic exercise used by people with SCI outside a hospital. However, evidence regarding the specific effects of ACE alone on fitness and health in adults with SCI is currently lacking. Hence, this review aimed to determine the effects of ACE on cardiorespiratory fitness, body composition, cardiovascular disease (CVD) risk factors, motor function, health-related quality of life (QoL), and adverse events in adults with chronic SCI. Inclusion criteria were: inactive adults (≥18 years) with chronic SCI (>12 months post injury); used ACE alone as an intervention; measured at least one of the following outcomes; cardiorespiratory fitness, body composition, cardiovascular disease risk factors, motor function, health-related QoL, and adverse events. Evidence was synthesised and appraised using GRADE. Eighteen studies with a combined total of 235 participants having an injury between C4 to L3 were included. There was a moderate certainty of the body of evidence on ACE improving cardiorespiratory fitness. Exercise prescriptions from the included studies were 30-40 minutes of light to vigorous-intensity exercise, 3-5 times per week for 2-16 weeks. GRADE confidence ratings were very low for ACE improving body composition, CVD risks factors, motor function, or health-related QoL. No evidence suggests ACE increases the risk of developing shoulder pain or other injuries. Overall, this review recommends adults with chronic SCI should engage in regular ACE to improve cardiorespiratory fitness. More high-quality, larger-scale studies are needed to increase the level of evidence of ACE in improving cardiorespiratory fitness and to determine the effects of ACE on other outcomes.